A study of Mentalization based on Attachment Styles, Ego Strength, Object Relations and Pattern of Anxiety Manifestation in Students - Mahgol Shojaei; َAkram Dehghani (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2023)
Aim and Background: Mentalization capacity is necessary for empowering students in interpersonal interactions and consequently obtaining future success, and for this reason, it is necessary to know its correlates, Therefore The purpose of the current research was to investigate the mentalization based on attachment styles, Ego strength, Object relations and Pattern of anxiety manifestation in students. Methods and Materials: The research community was formed by the students of Isfahan National University and Azad University in 2022, according to the latest reports, their number is 35161. Based on Cochran's formula, 380 students were selected as available. The research tools were Attachment Styles Questionnaire (ASQ), Psychosocial Inventory of Ego Strengths (PIES), Bell Object Relations Inventory (BORI), Anxiety Manifestation Patterns Questionnaire and Reflective Functioning Questionnaire (RFQ) which were completed individually by students. Data analysis was done by multiple regression analysis using the twenty-sixth version of SPSS software. Findings: The results showed that secure and ambivalent attachment styles as well as ego strength can significantly predict students' mentalization capacity. (p<0.05). Conclusions: Therefore, in order to improve students' mentalization, it is necessary to pay attention to secure and ambivalent attachment styles as well as ego strength.